Disruption of the Choroid Plexus Circadian Rhythm’s in Alzheimer’s Disease - Furtado, André Filipe Lino (2019)
Alzheimer´s disease (AD) is a neurodegenerative disorder, characterized by amyloid beta (Abeta) and tau protein deposition in the brain parenchyma and blood vessels. Abeta accumulation in areas of the brain controlling circadian rhythms can delay or shift activity rhythms. The circadian rhythm is coordinated by the master circadian pacemaker located in the suprachiasmatic nucleus (SCN) of the hypothalamus. The choroid plexus (CP), a recent characterized extra-SCN circadian oscillator, is also known to exhibit morphological changes in AD which are exacerbated by the presence of Abeta deposits in CP epithelial cells. Melatonin is a hormone secreted by the pineal gland and there’s some evidence that, in AD patients, the circulating levels of this hormone are diminished. Under normal circumstances, melatonin acts as a neuroprotector against AD, but how this protection occurs is still to be fully comprehended. It also acts as a Zeitgeber, synchronizing the rhythms of the circadian genes, regulating the body’s circadian clocks. In this study we addressed the question whether Abeta contributes to CP’s circadian clock disruption and if melatonin modulates circadian clock genes expression therein. Using an AD mouse model (APP/PS1), we investigated changes in the expression of CP clock genes at different time points, in female and male animals, aged 6 and 12 months old. In addition, in vitro studies using Z310 cell line treated with Abeta and melatonin were used to examine if melatonin modulated Bmal1 circadian expression. We demonstrated that only Bmal1 circadian expression is altered in AD mice model 12 months old. Contrarily, Cry2 and Per2 expression were not affected in the APP/PS1 model. In addition, we found that melatonin modulated several parameters in the circadian expression of Bmal1. These results indicate that Abeta deposition on the CP disrupted the rhythmic circadian expression of Bmal1 and that melatonin modulates CP clock gene circadian rhythms in the presence of Abeta.